An evaluation of the use of EBT-XD film for SRS/SBRT commissioning of a 1.5 Tesla MR-Linac system. (April 2022) - Boh Lim, Seng; Tyagi, Neelam; Subashi, Ergys; Liang, Jiayi; Chan, Maria
Highlights: ERE has significant impacts on film dosimetry in a 1.5T MR-Linac. Applying water droplet technique to film dosimetry minimizes the ERE impact. EBT-XD films provide accurate small field dosimetry under ERE. Penumbra uncertainties can affect the SRS feasibility with a 1.5T MR-Linac. Abstract: Purpose: The goal of this study was to evaluate the use of EBT-XD film for SRS/SBRT commissioning in a 1.5T hybrid MR-Linac (MRL). Method: The output factors (St ), from 1x1, 2x2, 3x3 cm 2, were measured with film in solid water. The results were compared with (1) the measurements by a PTW diamond detector (CVD) and an Exradin® A26MR ion chamber in 3D water phantom; (2) Monte Carlo calculation by Monaco TPS (MTPS) in water. The inline (IN) and crossline (CR) profiles, measured by films and the CVD, were also compared. An SRS plan with two targets was created in MTPS and was measured with EBT-XD film in a StereoPHAN TM phantom serving as an end-to-end test. The 3x3 cm 2 was used for film calibration with doses ranging from 0 to 28 Gy. Water was added to the phantom-film-phantom interface to reduce the electron-return-effect (ERE). Films were calibrated with One-scan-dosimetry protocol. Results: The film St were within 1.2% and 2.2% compared to other detectors and MTPS respectively. At the central B-field induced asymmetric region, films were within 0.6% between the CVD and the MTPS, but 5–8% differences were observed in the 40%-5% gradient region in CR due to ERE. The differences in localization and dose were found to be 0.6 mm and 3.3%. The γ(3%/2mm), γ (5%/2mm), γ (5%/1mm) were 97.7%, 99.3%, 94.6%. Conclusions: Films can provide accurate dosimetric results under ERE and are valuable for commissioning MRL. Using the One-scan-dosimetry protocol with EBT-XD film for MRL increases accuracy and efficiency in commissioning and QA of SRS/SBRT.